Rehabilitation and Reconstruction Plan (2022-2024): The Implementing of Central Sulawesi Governor’s Regulation in Sigi Regency - Vidyanto Vidyanto; Muhammad Rizki Ashari; Christin Florensia Melang; Muhammad Ryman Napirah; Muhammad Nasir; Arwan Arwan (An Idea Health Journal, 2026)
Background: Central Sulawesi is one of the most disaster-prone regions in Indonesia. In Sigi Regency, Beka Village experienced repeated floods between 2018 and 2021, while post-disaster rehabilitation and reconstruction following the 2018 disaster reached only 70.77 percent, leading to the issuance of Central Sulawesi Governor Regulation No. 4 of 2022. This study aimed to analyze the implementation of rehabilitation and reconstruction policies in Beka Village. Methods: A qualitative case study approach was used involving informants from the Sigi Regional Disaster Management Agency (BPBD), the Ministry of Public Works and Housing, and the Beka Village Government. Data were collected through in-depth interviews, observations, and document reviews, and analyzed using content analysis with triangulation techniques. Result: The findings show that policy communication and clarity were generally adequate, although consistency among implementing agencies remained limited. Human resources, budgets, and facilities were sufficient, while leadership commitment and employee incentives supported implementation. However, weaknesses were identified in the bureaucratic structure, particularly the absence of sanctions for SOP violations and the lack of specific SOPs for rehabilitation and reconstruction activities. Conclusion: The implementation of Central Sulawesi Governor Regulation No. 4 of 2022 has not been fully effective, especially regarding communication and SOP availability. Improved coordination among implementing agencies is needed to accelerate rehabilitation and reconstruction efforts.